Experimental program and numerical assessment for determination of stress triaxiality and J3 effects on AA6101-T4. (April 2020) - Malcher, L.; Morales, L.L.D.; Rodrigues, V.A.M.; Silva, V.R.M.; Araújo, L.M.; Ferreira, G.V.; Neves, R.S.
Highlights: Experimental program for AA6101-T4. Stress triaxiality and normalized third invariant effects. Ductile fracture and finite elements analysis. Accumulated plastic strain at fracture indicator. Gao' model with isotropic hardening. Abstract: This article proposes the study of the mechanical behavior of AA6101-T4 at fracture for different stress states. Firstly, an experimental program has conducted including the design and manufacture of six different types of specimens to perform mechanical tests considering some levels of stress triaxiality and normalized third invariant. The specimens are the smooth and notched cylindrical bars under tensile loading and rectangular cross-section specimens under pure shear and combined tensile/shear loading conditions. Furthermore, the Gao' model assuming non-linear isotropic hardening has used to describe the mechanical behavior of the material in axisymmetric and tridimensional problems until the facture, regarding an implicit numerical integration scheme in a finite elements framework. Posteriorly, reaction curves obtained numerically have compared with curves observed in the experimental tests. Then, it has proposed a discussion about the influence of the stress triaxiality and normalized third invariant on the level of the accumulated plastic strain at fracture. Finally, the equivalent plastic strain at fracture has been analyzed as a fracture indicator in order to observe the correct fracture onset.